Change in functional status among children treated in the intensive care unit after injury. Issue 5 (May 2019) - Ahmed, Omar Z.; Holubkov, Richard; Dean, J. Michael; Bennett, Tellen D.; Meert, Kathleen L.; Berg, Robert A.; Newth, Christopher J.L.; Carcillo, Joseph A.; Burd, Randall S.; Pollack, Murray M.
Abstract : BACKGROUND: Because pediatric trauma-related mortality continues to decline, metrics assessing morbidity are needed to evaluate the impact of treatment after injury. Based on its value for assessing children with traumatic brain injuries and other critical illnesses, Functional Status Scale (FSS), a tool that measures function in six domains (communication, feeding, mental, motor, sensory, and respiratory), was evaluated as an outcome measure for the overall population of injured children. METHODS: Children with at least one injury (Abbreviated Injury Scale [AIS] severity ≥1) surviving to discharge between December 2011 and April 2013 were identified in a previous study of intensive care unit admissions. Morbidity was defined as additional morbidity in any domain (domain FSS change ≥2 or "new domain morbidity") and additional overall morbidity (total FSS change ≥3) between preinjury status and discharge. Associations between injury profiles and the development of morbidity were analyzed. RESULTS: We identified 553 injured children, with a mean of 2.0 ± 1.9 injuries. New domain and overall morbidity were observed in 17.0% and 11.0% of patients, respectively. New domain morbidity was associated with an increasing number of body regions with an injury with AIS ≥ 2 ( p < 0.001), with severe (AIS ≥ 4) head ( p = 0.04) and spine ( p = 0.01) injuries and with at moderately severe (AIS ≥ 2) lower extremity injuries ( p = 0.01). New domain morbidity was more common among patients with severe spine and lower extremity injuries (55.6% and 48.7%, respectively), with greatest impact in the motor domain (55.6% and 43.6%, respectively). New domain morbidity was associated with increasing injury severity score, number of moderately severe injuries and number of body regions with more than a moderately severe injury ( p < 0.001 for all). CONCLUSIONS: Higher morbidity measured by the FSS is associated with increasing injury severity. These findings support the use of the FSS as a metric for assessing outcome after pediatric injury. LEVEL OF EVIDENCE: Prognostic/Epidemiologic, level III.